A Procedural Model for Planning and Evaluating Behavioral Interventions - Hyner, G. C. (Methods of Information in Medicine, 2005)
Objective: A model for planning, implementing and evaluating health behavior change strategies is proposed. Variables are presented which can be used in the model or serve as examples for how the model is utilized once a theory of health behavior is adopted.Results: Examples of three innovative strategies designed to influence behavior change are presented so that the proposed model can be modified for use following comprehensive screening and baseline measurements. Three measurement priorities: clients, methods and agency are subjected to three phases of assessment: goals, implementation and effects.Conclusion: Lifestyles account for the majority of variability in quality-of-life and premature morbidity and mortality. Interventions designed to influence healthy behavior changes must be driven by theory and carefully planned and evaluated. The proposed model is offered as a useful tool for the behavior change strategist.
Keywords: Planning model; behavior change; evaluation